STO vs. ICO: A theory of token issues under moral hazard and demand uncertainty - Anton Miglo (Journal of Risk and Financial Management, 2021)
This paper considers a financing problem for an innovative firm that is launching a web-based platform. The entrepreneur, on one hand, faces a large degree of demand uncertainty on his product and on the other hand has to deal with incentive problems of professional blockchain participants who contribute to the development and sales of the product. We argue that hybrid tokens can be a better option for the firm compared to straight utility tokens or security tokens because they help the firm better deal with both the moral hazard problems (via profit sharing incentives) and demand uncertainty (they help the firm learn the market demand for the product). This finding is consistent with some recent evidence. The paper also generates new predictions regarding the effect of different variables on the choice of financing method that have not yet been tested.
Keywords: D82; G32; L11; L26; M13; 330; blockchain; demand uncertainty; entrepreneurial finance; FinTech; initial coin offering; moral hazard; security token offering